QUR’ANIC VALUES AS THE FOUNDATION OF ISLAMIC WORK ETHIC: A THEMATIC STUDY ON THE CONCEPTS OF ‘AMAL, AMANAH, AND ISTIQĀMAH - Ahmad M. Latief; Achmad Abubakar; Mardan (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine the Qur’anic perspective on work ethics, focusing on three core values: amanah (trust and responsibility), istiqāmah (consistency), and ikhlāṣ (sincerity). Using a thematic exegesis (tafsīr maudhu‘ī) approach combined with a comprehensive literature review, this research identifies Qur’anic verses related to work (‘amal) and contextualizes them within contemporary discussions on the Islamic Work Ethic (IWE). The findings reveal that, in Islam, work is regarded as an integral form of worship that must be carried out with honesty, consistency, and moral integrity. The value of amanah plays a central role in fostering trust and loyalty within organizations, while istiqāmah ensures the sustainability of ethical conduct, and ikhlāṣ instills a transcendental motivation that elevates professional dedication beyond material goals. Furthermore, the study demonstrates that the application of Qur’anic values in professional and educational settings can enhance productivity, job satisfaction, and the development of an ethical and healthy organizational culture. Overall, the study concludes that the Qur’anic work ethic remains profoundly relevant in addressing the professional and moral challenges of the contemporary global era.